Peran BUMDes Swadesa Arta Mandiri dalam Pemberdayaan Perekonomian Masyarakat dan Pembangunan Desa Wonomerto Kabupaten Lampung Utara Menurut Perspektif Ekonomi Islam - Alda Marfilia; Yulistia Devi; Eka Nova Astuti; Tsabitah Aliyah; Iqbal Wahyudin (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Villages have an important role in supporting the economy of a country, with a variety of potential that can be developed to improve the welfare of the community. One potential that can be utilized is livestock waste that can be processed into organic fertilizer. In Wonomarto Village, North Lampung Regency, there are other local resources with economic value, such as moringa and bitter melon leaves that can be processed into chips, as well as the use of livestock manure for compost production. To support the utilization of these resources, BUMDes Swadesa Artha Mandiri formed a business group that aims to assist the community in carrying out productive activities, such as processing goat manure into compost and processing moringa and bitter melon leaves into valuable products. This research uses a descriptive qualitative method that aims to provide a comprehensive picture based on data obtained through observation. The results show that community empowerment through BUMDes runs effectively through several stages, namely consultation, business group formation, training, and mentoring. With this program, the people of Wonomarto Village are able to optimally utilize local potential, including processing goat manure into compost, and developing processed products such as moringa chips and bitter melon chip.